Application of high-grade carbon produced from tyre waste using advanced thermo-chemical technology. (2021) - Sharma, Anita; Sharma, Abhishek; Joshi, Jyeshtharaj B.; Jain, Rakesh Kumar; Kasilingam, Rajkumar
Abstract: Advanced thermo-chemical treatment in inert environment (also known as pyrolysis) of end of life tyres results into generation of oil, non-condensable gases and carbonized product termed as char. Solid char accounts to 35–45 wt% of the total products depending upon the process conditions. The present study is directed towards evaluating the suitability of tyre char for certain commercial applications. Char contains additives (inorganics) which are used to enhance certain properties of commercial tyres. Characterization of char confirms the presence of 19% inorganics that constitutes of elements such as Zn, S, Mg, Si and Ca. The other characterization techniques such as Raman, SEM and TGA have assisted in examining the surface characteristics and stability of tyre char. Raman analysis has emphasized on the presence of graphitized carbon structure with lesser defects. TGA analysis has showed suitable thermal stability at higher temperatures. The direct application of tyre char without further treatment has been undertaken based on these analyses. Char obtained from tyre pyrolysis was evaluated in Styrene Butadiene Rubber based compounding formulation at a dose of 50 parts per hundred gram of Rubber in comparison with a standard carbon black grade of Semi Reinforcing type of carbon black with equivalent dose. It was found that the increase in tensile strength and associated properties of vulcanization of char sample and the char can be utilized in rubber products formulation without any negative impact. Significant improvement was observed on tear strength properties while adding the char or carbon black which proves that there exists the reinforcing characteristics of the char like standard carbon black. Based on these studies, it has been concluded that there is need for further upgradation of tyre char for application in dyes, coatings and activated carbon industries.